Leadership mindsets : innovation and learning in the transformation of schools - Kaser, Linda (London, United Kingdom : Routledge, 2009)
This volume outlines an alternative way of thinking about school leadership. It examines research evidence that leaders will find most useful and suggests how they might use this evidence to maximize their learning and the learning of their students.
Chapter1. Moving from sorting to learning : new mindsets required -- Chapter2. Intense moral purpose -- Chapter3. Trust : relationships first -- Chapter4. Inquiry : questions before directions -- Chapter5. Learning for deeper understanding -- Chapter6. Evidence-seeking in action -- Chapter7. Learning-oriented design -- Chapter8. Connecting mindsets : networked leadership .
Includes bibliographical references and index.
Keywords: SCHOOL MANAGEMENT AND ORGANIZATION